Delamination study between leadframe substrate and epoxy mold compound for small outline semiconductor packaging - Azizan, Suhaimi (2024)
Superior quality and reliable semiconductor integrated circuit (IC) packaging is required in electronic products especially for automotive applications due to the user safety concern. Therefore, improvement and controlling of IC package defects to reduce field application and reliability failure is essential. One of the defects that leads to this problem is package delamination. Delamination is a phenomenon where there is a gap or separation between two different interfacial surfaces. Poor adhesion between substrate and resin molding compound in IC packaging can cause serious quality issues which degrade the product and package quality. Hence, the purpose of this study is to identify the relation between surface texturing (roughening) on pre-plated leadframe (PPF) substrate and delamination issue in IC packaging assembly. The textured surface of pre-plated leadframe was prepared by the substrate supplier. In this study, four analyses were performed which analysis of surface morphology, wettability test (contact angle measurement), resin molding shear strength test and moisture-temperature reliability test. For surface morphology analysis, textured PPF substrate showed an average surface roughness of 284nm while standard copper (Cu) substrate showed only 174nm (average surface roughness). Meanwhile for the wettability test, textured PPF substrate showed the highest value of contact angle (71º) at room temperature compared to standard Cu substrate. However, at 175ºC temperature which was simulated according to inline IC assembly manufacturing condition (real manufacturing environment), the textured PPF substrate exhibited the lowest contact angle value which only 55º compared to standard Cu substrate (66º). Low contact angle value at inline simulation temperature (175ºC) indicated good wettability where the liquid was well dispersed on the solid surface (PPF substrate surface). Furthermore, high shear strength value was observed for textured PPF substrate (27-40kgf) compared to standard Cu substrate (8-13kgf). The final package reliability test revealed that no delamination was observed for textured PPF substrate samples. Nevertheless, this delamination issue was observed for standard Cu substrate samples. All the analyses findings agreed that the interfacial surface adhesion between substrate and molding compound was significantly improved via surface texturing. This pointed out that surface texturing (roughening) on PPF helps to eliminate and control the delamination by improving and providing good adhesion between mold compound and substrate surfaces. As a result, high quality and better reliability performance of IC package was produced and safe to be used in electronic products.